Phonological Analysis of Selected Town of Southwestern Leyte, Philippines - BORONG, NORLYN (International Journal of Arts, Sciences and Education, 2024)
This study aims to provide a phonological analysis of the suprasegmental phoneme in particular. In this work, phonological analysis was employed in a qualitative design. Participants' words, phrases, and sentences were analyzed to identify stress, pitch and intonation and juncture. The researcher gathered volunteers 65 years of age and older who were native to five communities in the Southwest region of Leyte. The researcher employed a wordlist, conducted interviews, and recorded word pronunciations using a recorder as tools. It was found that certain portions of Matalom had stress comparable to the city of Maasin City, Southern Leyte in the suprasegmental phoneme, and similarly, some areas of the town of Inopacan had similar to the stress of Cebu. The town of Bato, Hilongos and Hindang have the same stress. In terms of pitch and intonation, the suprasegmental phoneme in the barrio Agbanga, Sta. Fe, Cahagnaan at Tag-os have a different pitch and intonation compared to some barangays of Matalom. Only barangay Dawahon in the town of Bato has a distinct pitch and intonation. When speaking, Hilongos, Hindang, and Inopacan all use the same intonation. Furthermore, there is no modification or difference during the pause or juncture. In conclusion, there is diversity in stress and intonation but not in pause or juncture among the phonological qualities, particularly in the suprasegmental phoneme, according to stress, pitch and intonation and juncture in the five towns of Southwestern Leyte. The results shows that the individual can change his accent and speech pattern (pronunciation) to fit changing circumstances, geographical limitations, and needs. It was shown that there is a regional correlation between the phonological variance in stress, pitch and intonation found in the Southwestern language of Leyte. In the findings, the researcher recommended using the words gathered in phonology classes to help students understand the distinctive features of the Leyte language and, more importantly, to help conserve or preserve the native tongue.